Investigating Related Risk Factors of Low-Back Pain Incidents Amongst Home-Tailors - Sari, Indah Permata; Runiasiwi, Des Anggraeni; Rachmawati, Utami (JURNAL CITRA KEPERAWATAN, 2023)
With 3.3 billion population worldwide is employed, several occupational disease (OD) and injuries ensued. Musculoskeletal Disorders (MSDs) is one among many ODs that hold high percentages among workers, and low back pain (LBP) raises as the main type of commonly found MSDs. This study aimed to investigates the relationship between the ergonomic risk factors and LBP complaints among home tailors at Desa Tembok Kidul Kecamatan Adiwerna Kabupaten Tegal, one of the host of home-tailors basis in Central Java. This descriptive correlative study using a cross sectional approach employed 139 home tailors as sample, selected with simple random sampling technique. A set of questionnaire was used and grouped into 3 part mainly measured the participants’ characteristics, ergonomic risk factors, and lastly LBP complaints. Validity and Reliability procedures proved the main two questionnaires were valid and reliable to use. With the main participants being a female (64,7%), most of them were coming from the young adults (64%), elementary school graduates (35,5%), the results of this study showed that there is no significant association between ergonomic risk factors and LBP complaints (p=1,000; α =0,05). However, this study emphasized that tailors with low ergonomic risk factors were less likely to have complaints of LBP than tailors with high ergonomic risk factors. Some possible ergonomic factors that goes along the growing number of LBP complaints are age, gender, and working duration. This study suggests to focus on one specific type of ergonomic risk factors to work with, while preventive measure on ergonomic-friendly working environment is advocated to alleviate the risk of OD.